Anatomy and Physiology of Farm Animals - Fails, Anna Dee (Wiley Blackwell, 2018)
"Revised and updated, the eighth edition of Anatomy and Physiology of Farm Animals remains the essential resource for detailed information on farm animal anatomy and physiology"--